The Role of Islamic Humanism in Shaping Students’ Character: An Islamic Educational Philosophy Approach - Slamet Panuntun; Fatah Syukur; Fatkuroji Fatkuroji (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study examines the decline of empathy, social responsibility, and moral awareness among students influenced by digital culture and increasing individualism. Grounded in Islamic educational philosophy, the research aims to analyze the implementation of Islamic humanism in student character development at MI Tegowanu and SDIT Al Firdaus Grobogan. The novelty of this study lies in its empirical case-study approach, which explores the internalization of Islamic humanistic values through educational practices, school culture, and institutional vision in Islamic elementary schools. This research employed a qualitative case study design. Data were collected through in-depth interviews, participatory observation, and document analysis involving principals, teachers, students, and foundation representatives. Data were analyzed using the Miles and Huberman interactive model, while triangulation and credibility tests were applied to ensure validity and reliability. The findings indicate that both schools successfully integrated Islamic humanistic values into daily educational activities despite the challenges of digital individualism and declining social empathy. Students demonstrated empathy, cooperation, discipline, respect, and social responsibility, grounded in the principles of tauhid and karamah insaniyah. The study concludes that Islamic humanism effectively strengthens character education through curriculum integration, teacher mentoring, a supportive school culture, and institutional commitment, providing a practical, replicable framework for Islamic elementary education.